2021
DOI: 10.2166/ws.2021.066
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nitrogen transport in the unsaturated zone with fluctuations in groundwater depth

Abstract: Fluctuations in groundwater depth play an important role and are often overlooked when considering the transport of nitrogen in unsaturated zone. To evaluate directly the variation of nitrogen transport due to fluctuations in groundwater depth, the prediction model of groundwater depth and nitrogen transport were combined applied by least squares support vector machine (LS-SVM) and Hydrus-1D in the western irrigation area of Jilin in China. The Calibration and testing results showed the prediction models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The investigations revealed that the soil water and N transport parameters had profile spatial variability (Bian et al, 2014(Bian et al, , 2021. Therefore, it is essential to explore the effects of parameter uncertainty on water transport and nitrate N leaching based on the GLUE method.…”
Section: Influence Of Parameter Uncertainty On Water and N Parameters...mentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations revealed that the soil water and N transport parameters had profile spatial variability (Bian et al, 2014(Bian et al, , 2021. Therefore, it is essential to explore the effects of parameter uncertainty on water transport and nitrate N leaching based on the GLUE method.…”
Section: Influence Of Parameter Uncertainty On Water and N Parameters...mentioning
confidence: 99%
“…Hence, there is still a lack of knowledge regarding the patterns of N transport and simulations in the vadose zone (Gai et al, 2019; Šimůnek, van Genuchten, & Sejna, 2016). The model is now considered an essential tool for the study of irrigated water fields, soil salinization and agricultural production, among others (Bian et al, 2021; Lekakis & Antonopoulos, 2015; Zhang et al, 2020). The HYDRUS model has been developed with several numerical modules that simulate the transport of energy, moisture and solute in saturated porous media (Phogat et al, 2020; Šimůnek et al, 2013; Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this SI brings advances in precision irrigation techniques adapted to the actual needs of plants at farm and extended scale applications (Filintas et al 2021;Markos & Radoglou 2021;Mousabeygi et al 2021). Also, new modelling approaches to predict and/or monitor water dynamics (Kader et al 2021;Mridha & Rahman 2021;Sihag et al 2021;Tziatzios et al 2021;Xu et al 2021) or pollutants transport such as salinity (Daghari et al 2021;Yuan 2021) and nitrates (Bian et al 2021;Nie et al 2021) are provided. An important part of this SI is covered by optimal water allocation and the newest developments in irrigation management (Cortés-Ruiz & Azuz-Adeath 2021;Lyra et al 2021;Mahdavi 2021;Morianou et al 2021a;Wei et al 2021).…”
Section: This Special Issuementioning
confidence: 99%
“…Frequently, modeling efforts are coupled with inverse parameter estimation of soil hydraulic properties (SHPs) (e.g., Forkutsa et al., 2009; Karimov et al., 2014; Kelleners et al., 2005; Schwärzel, Šimůnek, van Genuchten et al., 2006). Various other conditions have been applied at the lower BCs, including (i) no flow—this condition is especially employed in investigations related to actual evapotranspiration (ET a ) or air entrapment (Dettmann et al., 2014; Schwärzel, Šimůnek, Stoffregen et al., 2006; Zhang et al., 2011) and (ii) free drainage— this condition is used to study nutrient leaching (e.g., Bian et al., 2021; Jha et al., 2017). However, we did not come across any shallow groundwater modeling studies where variable flux conditions were applied based on inflow and outflow measurements at the lower boundary.…”
Section: Introductionmentioning
confidence: 99%